Update on the use of allergen challenge chambers in immunotherapy: clinical implications. Issue 2 (21st April 2022) - Zieglmayer, Petra U.; Pfaar, Oliver
Abstract : Purpose of review: This review aims to reflect on and discuss recent evidence of applicability of allergen exposure chambers (AEC) for allergen immunotherapy studies, especially focussing on validation of AECs, technical documentation and future perspectives. Recent findings: Publications covered by this review summarize the historical background, current status of research use and validation of AEC systems. It describes identified unmet needs regarding comparability of AEC systems, reproducibility of clinical assessments and correlation of AEC-induced symptoms with scores under natural environmental exposure. Furthermore, new information on technical specifications, for example, dimensions, allergen dispersal and validation procedures is highlighted and future activities of the EAACI AEC task force group regarding harmonization of clinical endpoints are delineated. Summary: AECs are in use for evaluation of allergic patients for over three decades now. As different systems largely vary regarding technical set up and standard assessments, detailed technical documentation must be available. To gain acceptance of regulatory authorities for pivotal immunotherapy trials conducted with the use of AEC system, harmonization of clinical assessments as well as documentation of correlation of clinical AEC outcomes with environmental exposure clinical scores is required.